2020
DOI: 10.3389/fpsyt.2020.00872
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Is a Feasible, Safe, and Acceptable Intervention in Doctors and Nurses Working Nightshifts: The MIDNIGHT Trial

Abstract: Nightshift working is associated with sleep deprivation, fatigue and attention/ concentration deficits which, in healthcare workers, may impact on patient safety. Clinical staff in the UK routinely work several 12 h nightshifts in a row at about 1-3 month intervals. We investigated the feasibility and acceptability of a crossover trial of melatonin administration in clinical staff working nightshifts with an exploration of effects on sleep measures and attention/concentration tasks. This was a pilot, double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Of key clinical interest is whether low levels of melatonin may have a role in diseases of pregnancy. Administration of exogenous melatonin appears free of side effects in healthy non-pregnant subjects ( 20 , 31 ) and an open label phase I single arm trial of exogenous melatonin in women with pre-eclampsia reported that melatonin was safe for mothers and fetuses ( 5 ). Exactly how melatonin may be involved in the pathophysiology of pregnancy is vital to before moving on to ascertain the potential for exogenous melatonin as a therapy to prevent adverse obstetric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of key clinical interest is whether low levels of melatonin may have a role in diseases of pregnancy. Administration of exogenous melatonin appears free of side effects in healthy non-pregnant subjects ( 20 , 31 ) and an open label phase I single arm trial of exogenous melatonin in women with pre-eclampsia reported that melatonin was safe for mothers and fetuses ( 5 ). Exactly how melatonin may be involved in the pathophysiology of pregnancy is vital to before moving on to ascertain the potential for exogenous melatonin as a therapy to prevent adverse obstetric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, VSH disturbance scores are reported to be around 100-200. 14,15 Conversely, more than 60% of our participants had an efficiency score of <300 out of 600, and nearly one quarter (n=12) had a score of <150. Again, these scores are considerably lower than in people without chronic pain.…”
Section: Discussionmentioning
confidence: 69%
“…After reviewing the full text, we selected a final list of 32 studies ( Figure 1 ). Of these, 15 (46.9%) were cross-sectional surveys [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], 11 (34.4%) were RCTs [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], 4 (12.5%) were quasi-experimental studies [ 35 , 36 , 37 , 38 ], and 2 (6.3%) were cohort design studies [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 2822 adults were included in the final 32 studies. The study population of night-shift workers included health care workers (n = 18, 56.3%) [ 10 , 12 , 13 , 15 , 18 , 21 , 24 , 25 , 27 , 29 , 31 , 32 , 33 , 35 , 36 , 38 , 39 , 40 ], production workers (n = 6, 18.8%) [ 11 , 14 , 19 , 20 , 22 , 30 ], transportation workers (n = 3, 9.4%) [ 17 , 20 , 28 ], mixed types of workers (n = 1, 3.1%) [ 23 ] and no specific types of workers (n = 4, 12.5%) [ 9 , 16 , 26 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation